Multi-objective optimal RFID reader deployment using a Leaders and Followers algorithm. (September 2021) - Mathaba, T.N.D.
Abstract: The Radio Frequency Identification (RFID) reader deployment problem (RDP) is a key challenge in the planning of RFID networks. The majority of the current research uses metaheuristic algorithms to solve the multi-objective RDP for unconstrained deployment of readers possessing omnidirectional antennae. The increasing adoption of the Internet-of-Things (IoT) technology and smart directional antennae will make the RDP even more challenging. The contributions of this work are: firstly, modelling a novel RDP formulation as a mixed-integer nonlinear program (MINLP); secondly, incorporating both directional and omnidirectional antenna models into the RDP; and, lastly, introducing an adapted Leaders and Followers (LaF) solution algorithm for the RDP. The proposed LaF algorithm results in reduced energy use and interference reduction in comparison to other popular metaheuristic algorithms. The proposed MINLP model is also used to demonstrate the advantage of deploying readers possessing diverse antennae coverage compared to the exclusive use of omnidirectional antennae. Graphical abstract: Highlights: Optimal Radio Frequency Identification (RFID) reader deployment is multi-objective. Deployment can be modelled as a mixed-integer nonlinear program. A Leaders and Followers algorithm solves directional antennae placement. Optimal solutions are energy efficient and have lower interference.